Kewenangan Jaksa Dalam Menghentikan Penuntutan Demi Keadilan - Dewi, Dessy Kusuma (Diktum: Jurnal Ilmu Hukum, 2021)
The purpose of the research is to know the authority of prosecutors in applying restorative justice and what are the limitations of criminal acts can be done restorative justice efforts. The research uses a type of literature research with a normative approach that is analyzed qualitatively. The results showed that the Public Prosecutor (JPU) has the right to stop the prosecution of defendants in certain cases, if the victim and the accused agree on peace as stipulated in The Attorney General of the Republic of Indonesia Regulation No. 15 of 2020 Restorative justice approach, victims and perpetrators of criminal acts are expected to achieve peace by putting forward a win-win solution The limitation of a criminal offense can be done termination of prosecution with a restorative justice approach provided that the perpetrator is not a recidivist, his criminal acts are threatened with a fine or threatened with a prison sentence of not more than five years, criminal acts committed with the value of evidence or loss value of not more than 2.5 million rupiahs. The peace process is conducted by the parties voluntarily, with deliberations for consensus, without pressure, coercion, and intimidation. In the peace process, the Public Prosecutor serves as a facilitator which means that it has no interest or connection with the case, victim, or suspect, either personally or professionally, directly or indirectly.